2015
DOI: 10.1039/c4ra14602f
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-targeted co-delivery of mitomycin C and 10-hydroxycamptothecin via micellar nanocarriers for enhanced anticancer efficacy

Abstract: Polymer–lipid hybrid micelles co-delivered hydrophilic mitomycin C and hydrophobic 10-hydroxycamptothecin showed improved cellular uptake and cytotoxicity in vitro and enhanced tumor accumulation and antitumor activity in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The result of in vitro cell viability study presented that the MMC/HCPT loaded FA-micelles demonstrated time-and concentration-dependent cytotoxicity. The cytotoxicity of combined drugs is significantly enhanced compared to both the free drugs and necessarily deters tumour growth than free drugs 65 as represented in Figure 5. MMC-SPC complex loaded phytosomes (MMC-loaded phytosomes) as drug carriers were surfacemodified with folate-PEG (FAPEG) to attain reduced toxicity and a superior MMC mediated therapeutic effect.…”
Section: Mitomycin Cmentioning
confidence: 94%
“…The result of in vitro cell viability study presented that the MMC/HCPT loaded FA-micelles demonstrated time-and concentration-dependent cytotoxicity. The cytotoxicity of combined drugs is significantly enhanced compared to both the free drugs and necessarily deters tumour growth than free drugs 65 as represented in Figure 5. MMC-SPC complex loaded phytosomes (MMC-loaded phytosomes) as drug carriers were surfacemodified with folate-PEG (FAPEG) to attain reduced toxicity and a superior MMC mediated therapeutic effect.…”
Section: Mitomycin Cmentioning
confidence: 94%
“…MTX + MMC codelivery using chitosan nanoparticles showed synergistic killing efficacy when tested against monodelivery of MTX and MMC [ 114 ]. In another study, Lin et al co-delivered MMC with 10-hydroxycamptothecin (HCPT) using folate functionalized soybean phosphatidylcholine micellar nanoformulation to test the therapeutic efficacy in HeLa Cells [ 115 ]. Direct cellular targeting of MMC and HCPT using micellar nanoparticles not only enhanced cellular uptake in in vitro and in vivo but also showed significant reduction in tumor burden compared to free drugs.…”
Section: Cellular Level Targetingmentioning
confidence: 99%
“…The delivery of MMC through nanodrug delivery systems (including nanoparticles, polymer micelles, liposomes, and dendrimers, etc.) can significantly improve its targeting, change the biological distribution of the drugs, reduce the distribution of the drugs in normal tissues, and also increase the accumulation and retention time of drugs in tumor sites [9][10][11][12][13]. Because of the water-soluble characteristics of MMC, most MMC is first modified into prodrugs or lipid complexes, and then loaded with liposomes or encapsulated with nanoparticles (NPs) by the double emulsion solvent diffusion technique, or others [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…can significantly improve its targeting, change the biological distribution of the drugs, reduce the distribution of the drugs in normal tissues, and also increase the accumulation and retention time of drugs in tumor sites [9][10][11][12][13]. Because of the water-soluble characteristics of MMC, most MMC is first modified into prodrugs or lipid complexes, and then loaded with liposomes or encapsulated with nanoparticles (NPs) by the double emulsion solvent diffusion technique, or others [13][14][15][16][17]. However, most of the drug delivery methods of MMC reported in the literature have a low encapsulation efficiency, and it is difficult to maintain the stability of the drug in the carrier [16,17].…”
Section: Introductionmentioning
confidence: 99%